Australia - Grace Jones (India Booklife, 2018)
Learn about some of the most endangered animals in the world and the continents tat they live on. This series uses eye-catching imagery, informative diagrams and fascinating facts to bring key subject areas to life. It explores the reasons why some species are endangered and the steps that are being taken to ensure these species do not become extinct in the future.
Keywords: Global Issues -- Global Issues; Threat To Animals -- Threat To Animals